Transformations in Medieval Fez: Almoravid Hydraulic System and Changes in the Almohad Walls. - Marcos-Cobaleda, María; Villalba Sola, Dolores (Routledge, 2017)
During the Almoravid and Almohad periods, Fez acquired a great importance which was materialised in a great number of constructions and transformations in the town. The aim of this paper is to discuss the significance of these medieval works and their importance in the development of Fez between the 11th and 13th centuries. In this way, we analyze two samples of these works: the Almoravid hydraulic system built by Yūsuf Ibn Tāšufīn, including the ‘water dispenser’ of Būjlūd, and the Almohad transformations in the military constructions of Fez, especially the defensive system of Bāb Sāgma. Beyond a brief historical introduction of the city during the Almoravid and Almohad periods, a section about written and archaeological sources and the detailed description of both constructions, we have included a discussion section with the interpretation of the main reasons why the Almoravids and Almohads developed this kind of works in the town. This fact was related to religious and political reasons, deeply connected to the ideas of control, power and exaltation of governors of both dynasties. Moreover, we include the analysis of the type of decoration known as ‘false bonding’ (falso despiece) that appears in the complex of Bāb Sāgma. For the presence of this ornamentation, typically used during the Almohad period, as well as for the references of the written sources, we propose a revision of the traditional Merinid chronology suggested for this military construction.
https://openpolicyfinder.jisc.ac.uk/id/publication/6187
Keywords: Arquitectura militar - Fez (Marruecos); Estructuras hidráulicas - Fez (Marruecos); Almorávides; Almohades; Almoravids; ‘False bonding’ (falso despiece) decoration; Hydraulic constructions; Military construction